Social work science - Shaw, Ian, 1945- (Columbia University Press, 2016)
What is the role of science in social work practice and what does it add to research in the field' Ian Shaw threads together advances in modern technology, practice skills and evidence-based practice, the history of scientific claims in social work practice, and the methods of social work research to demonstrate the significant role science can play in the management of human emotions and behavior. By treating science as a social action marked by the interplay of choice, activity, and constraints, Shaw links scientific and social work knowledge through the core themes of quality evidence, critical learning and understanding, and the skilled evaluation of the subject. He shows specifically how to connect science, research, and practice and speaks to the novel topics this integration introduces into the discipline, including a focus on expertise and the benefits of tacit knowledge and understanding.